DETERMINANTS OF WOMEN PARTICIPATION IN RICE PROCESSING MARKETING IN MAKURDI LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA - Ochimana, G. A.; Musa, A. U.; Sunday, T.D. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was carried out to analyse the determinants of women in rice processing marketing in Makurdi Local Government Area of Benue State, Nigeria. The sample size of 120 respondents was selected through a multistage sampling procedure. Data for the study were collected using a structured questionnaire through interviews on-the-spot methods. Data was analysed using descriptive and inferential statistics. The results on socioeconomic characteristics of women rice processors marketers revealed the mean age of 42years, most (85.0%) were married with a household size, farm size, years spent in school, farming experience of 7 persons, 3.5hectares, 7.45 years 28years respectively. Majority (67.5%) of respondents were traders, with a mean annual total stock of 2875 kg, an annual income of N363,458.33, 88.3% 76.7% has no access to credit extension services, respectively. The result on activities performed by women in rice processing marketing revealed majority (100%) performed transportation, soaking of rice for parboiling, parboiling of rice milling of rice. The semilog regression result on women participation in rice processing marketing showed that age (-0.243), educational qualification (0.905), quantity of paddy rice stock (1.012) consumers purchasing power (0.828) were statistically significant determinants (P<0.01). The result on the benefit cost ratio on profitability of rice processing marketing by women showed total variable cost (TVC) of N556,382.474, total revenue (TR) of N619,841.67, gross margin (GM) of N63,459.196 benefit cost ratio (BCR) of 1.11 (>1). The multiple response result on challenges encountered by women in rice processing marketing showed majority (100%) were price fluctuation, low quality paddy rice for milling, inadequate marketing infrastructure lack of capital. The study concluded that women play a vital role in rice processing marketing, actively engaging in key activities such as transportation, soaking, parboiling, milling. The findings also revealed that determinants of participation included age, education, paddy rice stock, consumer purchasing power. It is therefore recommended that women rice processors marketers should be given greater access to affordable credit facilities through microfinance institutions, cooperatives, government interventions to enhance their operational capacity.